Suicide in Chile: from macro to micro - Luciano Ferreira Rodrigues Filho; Graciela Rojas (Semina: Ciências Sociais e Humanas, 2025)
Suicide is a critical public health issue, representing one of the leading causes of death globally, with significant biopsychosocial implications. This study analyzes the phenomenon in the Chilean context, exploring risk factors such as socioeconomic inequalities, mental health, trauma, and cultural stigmas. The methodology included the analysis of national statistical data from 2000 to 2020, qualitative interviews with 186 individuals, and a bibliographic review of recent scientific publications. The results highlight the relevance of factors such as family support, experiences of violence, educational challenges, and economic crises in shaping suicide rates. The research reinforces the need for intersectoral strategies, including emotional interventions in education, inclusive public policies, and strengthening of support networks, to reduce the prevalence of suicide and promote mental well-being.